Statin‐Induced Impairment of Monocyte Migration Is Gender‐Related. Issue 12 (December 2014) - Ruggieri, Anna; Gambardella, Lucrezia; Maselli, Angela; Vona, Rosa; Anticoli, Simona; Panusa, Alessia; Malorni, Walter; Matarrese, Paola
<x xml:space="preserve">Abstract</x> Statins, widely used for treatment of hypercholesterolemia, have been demonstrated to exert pleiotropic beneficial effects independently of their cholesterol‐lowering action, such as anti‐inflammatory activity. A gender disparity has been observed in their cholesterol lowering activity as well as in response to these "off label" effects. Monocytes play a central role in atherosclerotic disease and, more in general, in inflammatory responses, through their chemotactic function and cytokine production. On these bases, in the present work, we examined the effect of statins on homeostasis and migration properties of freshly isolated monocytes from male and female healthy donors. Two prototypic natural and synthetic statins with different polarity, that is, type 1 and type 2 statins, have been considered: simvastatin and atorvastatin. Freshly isolated monocytes from peripheral blood of male and female healthy donors were treated with these drugs in the absence or presence of lipopolysaccharide (LPS) stimulation. Results obtained indicated that the polar statin efficiently inhibited chemotaxis of monocytes more than the apolar statin and that this effect was more significantly induced in cells from females than in cells from males. Dissecting the mechanisms involved, we found that these results could mainly be due to differential effects on: (i) the release of key cytokines, for example, MCP‐1 and TNF‐α; (ii) the maintenance of the redox homeostasis; (iii) a target activity on microfilament network integrity and function. All in all these results could suggest a reappraisal of "off‐label" effects of statins taking into account either their chemical structure, that is, molecular polarity, or the gender issue. J. Cell. Physiol. 229: 1990–1998, 2014. © 2014 Wiley Periodicals, Inc.